Crystal structure, in silico molecular docking, DFT analysis and ADMET studies of N-(2-methoxy-benzyl)-acetamide - Murugan, Suganya; Gunasekaran, Prasanth; Nehru, Jayasudha; Paul, Anaglit Catherine; Dege, Necmi; Cinar, Emine Berrin; Kavitha, Savaridasson Jose; Balasubramani, Kasthuri; Thanigaimani, Kaliyaperumal; Rajakannan, Venkatachalam; Hemamalini, Madhukar (European Journal of Chemistry, 2022)
In this work, N-(2-methoxy-benzyl)-acetamide (2MBA) was synthesized from an amide derivative and it was characterized by FT-IR and NMR spectroscopy techniques. The crystal structure of 2MBA was also validated via single-crystal X-ray diffraction analysis. Crystal data for C10H13NO2 for 2MBA: Monoclinic, space group P21/n (no. 14), a = 9.1264(6) Å, b = 9.3375(7) Å, c = 11.9385(8) Å, β = 95.745(5)°, V = 1012.26(12) Å3, Z = 4, μ(MoKα) = 0.082 mm-1, Dcalc = 1.176 g/cm3, 5632 reflections measured (5.368° ≤ 2Θ ≤ 51.992°), 1990 unique (Rint = 0.0377, Rsigma = 0.0314) which were used in all calculations. The final R1 was 0.0583 (I > 2σ(I)) and wR2 was 0.1444 (all data). The intermolecular interactions in 2MBA were theoretically examined by Hirshfeld surface analysis and 2D fingerprint plots. Moreover, the HOMO and LUMO energy gaps of 2MBA was calculated by DFT calculation with the B3LYP/6-311G++(d,p) method. The electron-withdrawing and donating sites of the 2MBA were confirmed via molecular electrostatic potential surface analysis. The present study discusses the title compound not only highlighted the crystallographic data but also revealed good molecular interactions together with an anticancer drug target, which is a targeting PARP protein, which was an important drug target in the treatment of breast cancer.